Penerapan Arsitektur Metafora Pada Perspustakaan Umum Di Kota Medan - Rivaldi Alyardho Panjaitan; Neneng Yulia Barky; Suprayitno (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2022)
A public library is a library designed for a wide audience as a means of lifelong learning, regardless of socio-economic background, race, religion, age, or gender. At this time, the willingness of Indonesian people to read is very worrying. This can be seen from the comparison of the willingness to read of the residents of Medan City, which is 1:1000. Therefore, it is planned to create or design a library with a national standard in the city of Medan. The application of the Metaphor Architecture Theme is taken from various points of view from a book, ranging from arranged books and open books, which have the meaning as a place for book collections and a place to read books that provide knowledge or information for free. This building also takes the basic shape of a square which means that the square has a formal impression and status according to the function of the building. Easy to expand, process structure and save space.